2018
DOI: 10.1097/pgp.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

An Ovarian Adenocarcinoma With Combined Low-grade Serous and Mesonephric Morphologies Suggests a Müllerian Origin for Some Mesonephric Carcinomas

Abstract: Mesonephric carcinomas are rare adenocarcinomas of the female genital tract that occur most commonly in the uterine cervix. They are classically thought to arise from benign mesonephric remnants, and are rarely reported at other sites in the gynecologic tract. Here we present an interesting biphenotypic ovarian adenocarcinoma with intimately associated but distinct components of both low-grade serous carcinoma and mesonephric-like carcinoma. A serous borderline tumor was present adjacent to the invasive carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(112 citation statements)
references
References 42 publications
8
102
2
Order By: Relevance
“…Another recently published two papers presented two ovarian adenocarcinomas with combined low-grade serous and mesonephric morphologies, also suggest a Müllerian Origin for some Mesonephric Carcinomas. [22,24] Given the previously documented association with endometriosis (ovarian neoplasms) [24] and the prominent endometrial involvement (uterine corpus neoplasms) [21] , these tumors are best regarded as of Mullerian origin and representing adenocarcinomas which differentiate along mesonephric lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recently published two papers presented two ovarian adenocarcinomas with combined low-grade serous and mesonephric morphologies, also suggest a Müllerian Origin for some Mesonephric Carcinomas. [22,24] Given the previously documented association with endometriosis (ovarian neoplasms) [24] and the prominent endometrial involvement (uterine corpus neoplasms) [21] , these tumors are best regarded as of Mullerian origin and representing adenocarcinomas which differentiate along mesonephric lines.…”
Section: Discussionmentioning
confidence: 99%
“…Mesonephric adenocarcinoma (MNAC) is a rare carcinoma that originates from mesonephric remnant of the female genital tract [1][2][3] , and are predominantly located on the lateral walls of the cervix and vagina [4] . Of the cases reported to date, the vast majority of MNAC are from uterine cervix [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] ., , comprising<1% of all carcinomas at this site [20] , several cases of MNAC are from ovary [21][22][23][24] , and rare cases are from vagina [4,7,[25][26][27][28][29] and uterine corpus [4,11,21,[30][31][32][33][34][35][36][37][38][39][40]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Recently, two studies reported single ovarian neoplasms with distinct areas of mesonephric-like carcinoma and serous borderline tumour/low-grade serous carcinoma. 66,67 In the two cases, both components contained an identical KRAS or NRAS mutation, suggesting that they were clonally related and did not represent collision tumours. It was concluded in both studies that it was likely that the serous tumour was the 'parent' neoplasm and that the mesonephric-like carcinoma developed from the serous component, and these studies provide additional evidence that mesonephric-like carcinomas are of Mullerian origin.…”
Section: Mesonephric-like Carcinomamentioning
confidence: 95%
“…Recently, two studies reported single ovarian neoplasms with distinct areas of mesonephric‐like carcinoma and serous borderline tumour/low‐grade serous carcinoma . In the two cases, both components contained an identical KRAS or NRAS mutation, suggesting that they were clonally related and did not represent collision tumours.…”
Section: Mesonephric‐like Carcinomamentioning
confidence: 99%